Privileged Quinolylnitrones for the Combined Therapy of Ischemic Stroke and Alzheimer's Disease - José M. Alonso; Alejandro Escobar-Peso; Alejandra Palomino-Antolín; Daniel Diez-Iriepa; Mourad Chioua; Emma Martínez-Alonso; Isabel Iriepa; Javier Egea; Alberto Alcázar; José Marco-Contelles (MDPI AG, 2021)
Cerebrovascular diseases such as ischemic stroke are known to exacerbate dementia caused by neurodegenerative pathologies such as Alzheimer's disease (AD). Besides, the increasing number of patients surviving stroke makes it necessary to treat the co-occurrence of these two diseases with a single and combined therapy. For the development of new dual therapeutic agents, eight hybrid quinolylnitrones have been designed and synthesized by the juxtaposition of selected pharmacophores from our most advanced lead-compounds for ischemic stroke and AD treatment. Biological analyses looking for efficient neuroprotective effects in suitable phenotypic assays led us to identify MC903 as a new small quinolylnitrone for the potential dual therapy of stroke and AD, showing strong neuroprotection on (i) primary cortical neurons under oxygen-glucose deprivation/normoglycemic reoxygenation as an experimental ischemia model; (ii), neuronal line cells treated with rotenone/oligomycin A, okadaic acid or β-amyloid peptide Aβ25-35, modeling toxic insults found among the effects of AD.